Biodeterioracja szkła wywołana przez zarodniki grzybów pleśniowych = Glass biodeterioration caused by mould spores - Piontek, Marlena; Łuszczyńska, Katarzyna; Lechów, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Microorganisms induce biodeterioration of both organic and inorganic building materials. From scientific literature it is clear that biological agents (mainly bacteria, cyanobacteria, mould spores and algae) settle on the surface of the glass, initiating in time the processes of its destruction. Biological corrosion is a consequence, among others.
Keywords: korozja biologiczna; biodegradacja szkła; mikroorganizmy; biological corrosion; biodeterioration of glass; microorganisms